Research on how entrepreneurial capacity and opportunity factors influence the intention of medical staff in the Mekong Delta to start a business in the healthcare sector - Phuc, Hung Nguyen; Thi My, Huong Vo; Tuyet, Minh Nguyen Thi; Anh, Tu Phan; Van, Anh Nguyen; Thuy, Quynh Huynh Thi; Nhu, Quynh Nguyen; Phu, Vinh Nguyen (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Entrepreneurship is increasingly being recognized as a solution to the challenges of the market economy, especially in the medical field.Study design. The study used a cross-sectional descriptive method with convenience sampling for data collection.Methods. The study employed random sampling for convenience based on output questions and in accordance with sampling criteria for the Mekong Delta provinces. The data was analyzed with SPSS version 20.0. This is done by calculating the Cronbach’s Alpha coefficient and applying the Exploratory Factor Analysis (EFA) method to identify the main factors, thereby determining the official set of questions for the study. EFA is used to find the relationship between independent and dependent variables, as these variables can affect the final results.Result. Gender: Females constitute 70.7% of the participants, while males make up 29.3%. Occupation: The majority of participants are pharmacists, accounting for 74.7% in the medical field. Business orientation: Among the businesses targeted by the participants, trading businesses account for 48.6%. The CFA results indicated good model fit: Tucker-Lewis Index = 0.945; Comparative Fit Index = 0.950, Goodness-of-Fit Index = 0.817 (> 0.8), Root Mean Square Error of Approximation = 0.069 (< 0.08), and Chi-Square Minimum Discrepancy divided by Degrees of Freedom = 4.980 (< 5), indicating a good fit with the actual data. The Structural Equation Modeling results include the following fit indexes: Chi-Square Minimum Discrepancy = 4.590; Comparative Fit Index = 0.955; Tucker-Lewis Index = 0.950; Goodness-of-Fit Index = 0.837; Root Mean Square Error of Approximation Root Mean Square Error of Approximation = 0.066; and Adjusted Goodness-of-Fit Index = 0.809. Entrepreneurial capacity factor and opportunities have a statistically significant impact on start-up intention, with significance levels